2021
DOI: 10.17532/jhsci.2021.1082
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Structure and Psychometric Properties of the Maslach Burnout Inventory (MBI) in Croatian Nurses

Abstract: Introduction: The role of nurses in healthcare is of great importance for the well-being of patients. Nurses are exposed to daily stress in the workplace due to the lack of staff, irregular working hours, and lack of support from the management. Such conditions greatly affect the emotional and psychological health of nurses. This study aims to explore the factor structure of the Maslach Burnout Inventory (MBI) on the Croatian sample of nurses.Methods: A cross-sectional study on the sample of 119 nurses, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Past investigations into the psychometric characteristics of the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) utilizing healthcare professional samples have yet to achieve consensus regarding the instrument's solid psychometric attributes. 10 Some studies confirm the 22-item three-factor structure, validity, and reliability of the MBI-HSS 11,12 ; other studies corroborate the three-factor model, but with elimination of some items. [13][14][15][16][17] Other studies have found a four-factor model 18 and a five-factor model.…”
Section: Brian Norman Peña Calero Universidadmentioning
confidence: 97%
See 2 more Smart Citations
“…Past investigations into the psychometric characteristics of the Maslach Burnout Inventory-Human Services Survey (MBI-HSS) utilizing healthcare professional samples have yet to achieve consensus regarding the instrument's solid psychometric attributes. 10 Some studies confirm the 22-item three-factor structure, validity, and reliability of the MBI-HSS 11,12 ; other studies corroborate the three-factor model, but with elimination of some items. [13][14][15][16][17] Other studies have found a four-factor model 18 and a five-factor model.…”
Section: Brian Norman Peña Calero Universidadmentioning
confidence: 97%
“…46 The subsequent five decades of research, albeit uncoordinated, have produced various definitions and measures of BS worldwide, leading to some inconsistencies. The principal tool for gauging BS is the MBI, 9 utilized across a range of populations, including the general clinical population, 11 healthcare professionals with versions such as the MBI-HSS, 31,47 the MBI-Medical Personnel (MBI-MP), and the MBI-General Survey (MBI-GS). The original questionnaire appraises three dimensions through a total of 22 items: EE (representing feelings of being emotionally overextended by one's work), DP (a disengaged and impersonal reaction towards patients), and PA (emotions of competence and successful achievement in one's profession).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… 46 The subsequent five decades of research, albeit uncoordinated, have produced various definitions and measures of BS worldwide, leading to some inconsistencies. The principal tool for gauging BS is the MBI, 9 utilized across a range of populations, including the general clinical population, 11 healthcare professionals with versions such as the MBI–HSS, 31 , 47 the MBI–Medical Personnel (MBI–MP), and the MBI–General Survey (MBI–GS). The original questionnaire appraises three dimensions through a total of 22 items: EE (representing feelings of being emotionally overextended by one's work), DP (a disengaged and impersonal reaction towards patients), and PA (emotions of competence and successful achievement in one's profession).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They have been further validated for human service professions, encompassing healthcare professionals. 11 , 31 , 47 …”
Section: Literature Reviewmentioning
confidence: 99%